Culture Negative Confoscan Positive Acanthamoeba Keratitis: A relentless course - Al Kharousi, Nadia S (Sultan Qaboos University Medical Journal, College of Medicine & Health Sciences, 2009)
Acanthamoeba keratitis is a protozoal infection of the eye, mainly due to the use of non-sterile solutions, like saline for disinfecting contact lenses. We report a case where delay in the diagnosis of acanthamoeba keratitis due to inadequate laboratory investigations and clinical management led to an excruciatingly painful course of the disease. The importance of non-invasive imaging techniques of confocal microscopy in the diagnosis of acanthamoeba keratitis, in the absence of positive culture reports, is highlighted in this case.